Thermal and non-thermal processing of red-fleshed apple: how are (poly)phenol composition and bioavailability affected?. Issue 12 (25th November 2020) - Yuste, Silvia; Macià, Alba; Motilva, María-José; Prieto-Diez, Neus; Romero, María-Paz; Pedret, Anna; Solà, Rosa; Ludwig, Iziar A.; Rubió, Laura
Abstract : This work fills a gap in the understanding of the effect of processing on the bioavailability of (poly)phenols in fruit products. Abstract : The present study evaluated the impact of different thermal (infrared-drying, hot air-drying and purée pasteurization) and non-thermal (freeze-drying) processing technologies on red-fleshed apple (poly)phenolic compounds. We further investigated the processing effect on the (poly)phenol bioavailability in a crossover postprandial study where three subjects consumed three apple products (freeze-dried snack, hot air-dried snack and pasteurized purée). (Poly)phenolic compounds present in the apple products and their biological metabolites in urine were analyzed using liquid chromatography coupled to mass spectrometry (UPLC-MS/MS). When comparing different processes, infrared-drying caused important losses in most of the apple (poly)phenolics, while hot air-drying and purée pasteurization maintained approximately 83% and 65% of total (poly)phenols compared with the freeze-dried snack, respectively. Anthocyanins in particular were degraded to a higher extent, and hot air-dried apple and pasteurized purée maintained respectively 26% and 9% compared with freeze-dried apple snack. The acute intake showed that pasteurized purée exhibited the highest (poly)phenol bioavailability, followed by hot air-drying and freeze-dried snack, highlighting the impact of processing on (poly)phenols absorption. In conclusion, for obtaining affordable new red-fleshed apple products with enhanced (poly)phenol bioavailability, purée pasteurization and hot air-drying represent viable techniques. However, to obtain a red-fleshed apple snack with high anthocyanin content, freeze-drying is the technique that best preserves them.